The determinants of bank's stock volatility - Topaloğlu, Emre Esat; Sakur, Resat; Yaman,Serdar (Peter Lang AG, 2020)
In this study, it is aimed to determine the factors that affect common stock volatility of banks. In this context, data of companies whose shares are traded in Borsa Istanbul Bank Index (XBANK) are analyzed for the period 2007:06-2018:09 using symmetrical and asymmetrical conditional variance models and panel data analysis. While the dependent variable of the study is common stock volatility, the independent variables are factors of profitability, valuation, financial structure, cost, and size as intrabank elements. As a result of the study, while a statistically significant and positive relationship was determined between common stock volatility and profitability, cost, and valuation rate, a statistically significant and negative relationship was detected between volatility and size. On the other hand, there was no significant relationship between volatility and financial structure. According to the results of the panel data analysis, while one unit increase in profitability, cost, and market value in banks led to an increase of 0.801, 0.085, and 0.025 units in common stock volatility, respectively, one unit increase in size caused a decrease of 0.018 units in stock volatility.
Keywords: Banks stock; GARCH models; Panel data analysis; Volatility